Development Strategy of Micro, Small and Medium Enterprises (MSMEs) Beujroh Based on Creative Economy in Increasing Community Income - Adhiana, Adhiana; Yanto, Nopri; Tanjung, Ade Firmansyah; Yundriana , Yundriana (Journal of Agriculture, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are key contributors to national economic growth due to their ability to absorb labor, generate income, and stimulate regional development. Beujroh MSME, located in Kutablang Village, Bireuen Regency, is an enterprise that preserves the cultural tradition of weaving using purun grass (Lepironia articulata) as its primary raw material. Its products, such as bags, hats, storage containers, coasters, and placemats, highlight the integration of traditional crafts with creative economic principles. This research aims to develop a strategic plan to support the growth of Beujroh MSME through a creative economy approach while identifying internal and external challenges faced by the business. Using a qualitative method and purposive sampling, this study applies SWOT analysis as the main analytical tool. The research is scheduled for August to December 2024 under the basic research scheme with Technology Readiness Level (TRL) 1–3. The results indicate that Beujroh MSME is in Quadrant I (growth strategy) with IFAS and EFAS scores of 0.31 and 0.64, respectively. Therefore, a Strength-Opportunity (SO) strategy is recommended, leveraging internal strengths to take advantage of external opportunities. Expected outputs include international and national journal publications and copyright registration, serving as strategic input for relevant stakeholders.